Secretion of secondary metabolite-like compounds by Burkholderia cepacia with antifungal activity against phytopathogens from commercial plants - Alexander Pérez Cordero; Donicer E.Montes Vergara; Yelitza Aguas Mendoza (International Journal of Medical Toxicology and Legal Medicine, 2024)
The objective of the present study was to evaluate the activity of secondary metabolites excreted by the endophytic bacterium Burkholderia cepacia against Colletotrichum gloeosporioides. The antifungal capacity of metabolite-type compounds obtained in modified culture media with different nutritional sources was evaluated. The results show an average inhibition of B. cepacia of 67.07% against the phytopathogenic fungus in contrast to the chemical control which was 61.35% against the phytopathogenic fungus C. gloeosporioides in the in vitro inhibition tests. A variety of secondary metabolites with antifungal activity against Colletotrichum are present in the extracts secreted by B. cepacia C. gloeosporioides